2018
DOI: 10.3390/s18113721
|View full text |Cite
|
Sign up to set email alerts
|

An EEG Experimental Study Evaluating the Performance of Texas Instruments ADS1299

Abstract: Texas Instruments ADS1299 is an attractive choice for low cost electroencephalography (EEG) devices owing to its low power consumption and low input referred noise. To date, there have been no rigorous evaluations of its performance. In this EEG experimental study we evaluated the performance of the ADS1299 against a high quality laboratory-based system. Two self-paced lower limb motor tasks were performed by 22 healthy participants. Recorded power across delta, theta, alpha, and beta EEG bands, the power rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 52 publications
2
51
0
Order By: Relevance
“…The latencies of BP1, BP2 and PN, and the amplitudes of BP1, BP2, PN obtained from the sum of the two ERPs at the latencies of BP1, BP2, time of PN provided the ground-truth data. A white noise was added to the sum of ERPs to produce simulated MRCPs under 3 signal to noise ratios (SNR) (6 dB, 3 dB, 0 dB) [31]. The signal to noise ratio was set by changing the root mean square value of the white noise with respect to the peak amplitude of the second ERP which corresponds to amplitude of PN.…”
Section: B Proposed Methods For Simulation Of Mrcpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latencies of BP1, BP2 and PN, and the amplitudes of BP1, BP2, PN obtained from the sum of the two ERPs at the latencies of BP1, BP2, time of PN provided the ground-truth data. A white noise was added to the sum of ERPs to produce simulated MRCPs under 3 signal to noise ratios (SNR) (6 dB, 3 dB, 0 dB) [31]. The signal to noise ratio was set by changing the root mean square value of the white noise with respect to the peak amplitude of the second ERP which corresponds to amplitude of PN.…”
Section: B Proposed Methods For Simulation Of Mrcpsmentioning
confidence: 99%
“…The experimental MRCPs used in this research were recorded from 22 healthy participants (Average age: 36 ± 6 years, 10 female) who were recruited through professional networks and local advertising [31]. Participants were excluded if they had a history of any neurological disorders or epilepsy.…”
Section: Experimental Mrcpsmentioning
confidence: 99%
“…Hence, the ability to record MRCPs and ERD is crucial for any neurorehabilitation BCI, and this ability has been less explored in commercial headsets. A single study compared the signal quality of MRCP when recorded with two different amplifiers but with the same headset [42], and a couple of studies investigated if ERD patterns could be identified using dry and wet electrodes [27,28]. Thus, there is a need for an evaluation of different headset types that potentially could be used for BCI training in neurorehabilitation clinics.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Oliveira et al [39] proposed a number of metrics to investigate the signal quality when comparing different headsets. These metrics include data or epoch rejection rate [16,39,40,43] and signal-to-noise ratio (SNR) or noise level [16,32,39,42,44]. This is also important for BCI applications, since the performances of pattern recognition techniques are affected by various types of noise that cannot be suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalography (EEG) is a means of obtaining data through sensors (Rashid et al, 2018 ; Uktveris and Jusas, 2018 ). The brain-computer interface (BCI), also known as a direct neural interface, is an interdisciplinary cutting-edge technology that represents a direct link between human or animal brains (or brain cell cultures) and external devices (Wolpaw et al, 2000 , 2002 ; Cecotti, 2011 ; Chaudhary et al, 2016 ; Ramadan and Vasilakos, 2017 ).…”
Section: Introductionmentioning
confidence: 99%